Factors affecting antiviral use of health workers diagnosed with COVID-19 in a university hospital - Tartar, Ayşe Sağmak; Kara, Kevser Tuncer; Uysal, Serhat; Akbulut, Ayhan; Demirdağ, Kutbeddin (Refik Saydam National Public Health Agency (RSNPHA), 2023)
Objective: COVID-19 turned into a pandemic in a short time. Healthcare workers are at risk of infection due to their contact with both patients and the society. The aim of this study is to examine the demographic structures of a hospital’s employees diagnosed with COVID-19, to examine the use of antiviral treatment and the factors affecting it, and to compare the case number curves of the hospital and the province. Methods: Healthcare workers who had been infected with the COVID-19 virus between 01.06.2020 and 28.02.2021 were included in the study. It is a cross-sectional, retrospective study. The patients were evaluated demographically and epidemiologically, and compliance treatment was examined in healthcare professionals who recommended antiviral drugs. Results: 390 (56.3%) of the 693 healthcare workers were males. Mean age of the patients was 33,54±9,41. 140 (20.2%) of them had chronic diseases. 173 (25%) were cigarette smokers. 161 (23.2%) individuals stated the source of infection as hospital. 509 (73.4%) had symptoms at the time of diagnosis while symptoms occurred later in 116 (16.7%). The most commonly observed symptoms included fatigue (48%), myalgia (47.5%) and headaches (46.9%). Of 693 patients, 164 (23.7%) did not use antiviral treatment. The distribution of the number of cases by months was similar when examined on the basis of hospitals and provinces. In the logistic regression analysis, those with symptoms at the time of diagnosis used antiviral treatment 1.779 times and those with chronic diseases 1.804 times more. Conclusion: The similarity of the case distribution in the society and among healthcare workers supports the effect of the use of personal protection equipment. In our study, it was observed that healthcare workers with risk factors for severe COVID-19 had higher adherence to antiviral treatment. Along with the vaccination activities and mutations, the clinical course and prognosis of the COVID-19 might change in time. Therefore, surveillance data should be collected from healthcare workers and evaluations should be made through interim analyses. Information about antiviral treatments should be given. © 2023. All Rights Reserved.; Amaç: 2019 yılında tanımlanan COVID-19, kısa sürede pandemiye dönüşmüştür. Sağlık çalışanları hem hastaları hem de toplumsal temasları sebebiyle risk altındadır. Bu çalışmanın amacı, bir hastanenin COVID-19 tanısı alan çalışanlarının demografik yapılarını, antiviral tedavi kullanımlarını ve etkileyen faktörleri incelemek; ayrıca hastane çalışanları ve ilimizin vaka sayısı eğrilerini karşılaştırmaktır. Yöntem: Çalışmaya, 01.06.2020-28.02.2021 tarihleriarasında COVID-19 geçirmiş olan sağlık çalışanları dahil edilmiştir. Kesitsel, retrospektif bir çalışmadır. Hastalar demografik ve epidemiyolojik açıdan değerlendirilmiş, antiviral ilaç önerilen sağlık çalışanlarında tedavi uyumu irdelenmiştir. Bulgular: 693 sağlık çalışanının 390 (%56,3)’ı erkekti. Yaş ortalaması 33,54±9,41 idi. 140 kişinin (%20,2) kronik hastalığı vardı. Hastalardan 173 kişi (%25,0) sigara kullanıyordu. Bulaş kaynağını 161 kişi (%23,2) hastane olarak belirtti. Tanı anında semptomu olanların sayısı 509 (%73,4) idi ve 116 kişiye (%16,7) tanı sonrası semptom eklenmişti. En sık görülen semptomlar halsizlik (%48), myalji(%47,5) ve baş ağrısı (%46,9) idi. 693 hastadan 164 kişi (%23,7) antiviral tedavi kullanmadı. Vaka sayılarının aylara göre dağılımı hastane ve il bazında incelendiğinde, benzerlik göstermekteydi. Lojistik regresyon analizinde tanı sırasında semptomu olanlar 1,779 kat, kronik hastalığı olanlar 1,804 kat daha fazla antiviral ilaç kullanmıştı. Sonuç: Toplumda ve sağlık çalışanlarında benzer vaka dağılımının görülmesi kişisel koruyucu ekipman kullanımının etkisiolarak değerlendirilmiştir. Çalışmamızda, ağır COVID-19 açısından risk faktörleri olan kişilerin antiviral tedaviye uyumunun daha yüksek olduğu görülmüştür. Zaman içinde aşılama çalışmaları ve mutasyonlar nedeniyle COVID-19 klinik seyri ve prognoz değişebilir. Bu sebeple sağlık çalışanlarında sürveyans verileritoplanmalı ve ara analizler ile değerlendirmeler yapılmalıdır. Antiviral tedaviler ile ilgili bilgiler verilmelidir. © 2023. All Rights Reserved.
Bir üniversite hastanesinde COVID-19 tanılı sağlık çalışanlarının antiviral kullanımını etkileyen faktörler
Keywords: COVID-19; COVID-19; favipiravir; favipiravir; healthcare workers; pandemi; pandemic; SARS-CoV-2; SARS-CoV-2; sağlık çalışanları